Macroinvertebrados associados às folhas em decomposição de riachos neotropicais: influência da qualidade química, variedade de espécies vegetais, biomassa de fungos e tempo de exposição - Biasi, Cristiane (2013)
In low-order freshwater ecosystems, macroinvertebrates have an important role in nutrient cycling, as they participate in the shredding of detritus, which are the main energy source for the trophic chain in these systems. This study aims to investigate the macroinvertebrate fauna associated to leaves of different plant species with different concentrarions of LigCel:N. Thus, we carried out four treatments. The first included Casearea sylvestris leaves and the second a mixture of C. sylvestris, Rollinia emarginata, Phytolacca dioica and Cabralea canjerana leaves. The third treatment consisted of Ficus luschnathiana leaves, and the fourth of a mixture of Trema micrantha, Inga alata, Cupania vernalis and F. luschnathiana leaves. The litter bags were used for the experiments, each containing 4.0 ± 0.1 g of leaves and after 7, 14, 21 and 28 days of incubation in the streams, four litter bags of each treatment were retrieved and analyzed. The leaves were washed for the removal of invertebrates, dried (30ºC) and destined for ergosterol analyses. All organisms were identified to the lowest possible taxonomic level and then classified in functional groups, according to feeding habits. Density of organisms, biomass and richness (through rarefaction) were determined, analyzed with a two-way ANOVA and then checked for correlations with fungal biomass using a Pearsons s Correlation test. Faunal composition was analyzed through MANOVA, NMDS, Cluster analysis and Indicator Species analysis. Significant differences were found among the treatments for macroinvertebrate density and Chironomidae density. The lower nutritional quality species (F. luschnathiana) presented the highest density and fungal biomass values and, consequently, the highest dry mass loss rate. We verified correlation between the density of organisms and fungal biomass. With this study, we verified that the macroinvertebrate community, as a whole, and also the Chironomidae specifically, are influenced by heterogeneity of the detritus and its chemical composition. However, microbial conditioning seems to be more important for this association, since it can increase the nutritional value of species typically considered of low palatability.